One-sided private provision of public goods with implicit Lindahl pricing - Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2010)
We consider a sequential game in which one player produces a public good and the other player can influence this decision by making an unconditional transfer. An efficient allocation requires the Lindahl property: the sum of the two (implicit) individual prices has to be equal to the resource cost of the public good. Under mild conditions this requires a personal price for the providing player that lies below half of the resource cost. These results can, for example, justify high marginal taxes on wages of secondary earners.
Keywords: C72; D61; H21; H41; 330; Lindahl pricing; noncooperative games; private provision of public goods; Stackelberg equilibrium; Soziale Wohlfahrtsfunktion; Öffentliches Gut; Allokationseffizienz; Duopol; Extensives Spiel; Nichtkooperatives Spiel; Theorie